Rutting behaviour in an enclosured group of wild forest reindeer (Rangifer tarandus fennicus Lönnb.) - Kojola, Ilpo (Rangifer, 1986)
The rutting behaviour of wild forest reindeer {Rangifer tarandus fennicus Lönnb.) was studied 1981 - 83 in a 15 ha enclosure located in Kivijärvi, Central Finland (63° N). The group consisted of two old stags, 6-9 hinds and their calves and yearlings. The main sections of the study were social structure, social signals, time budget and daily activity. In early September the aggressiveness of the stags towards females concentrated on those individuals which had last dominated them. Adult females were more aggressive to young females than to each other. The proposed aggressiveness of the hinds towards yearlings may be explained by the lower predictability of the hierarchial status of the young animals. The main character of observable social signals seemed to be similar to those described in earlier studies concerning the genus Rangifer. Stags often made snapping-like movements with their mouths during agonistic behaviour. Low-stretch displays and investigation of the urine of the females concentrated on the estrous hind during the day preceeding the pre-copulatory period (which commenced when the hind did not yet avoid the stag). The stag always sniffed at the vulva of the female after copulation. The harem stag did not stop grazing during the peak of the rut. Differences in the time budget between the dominant and subdominant stag as between estrous and anestrous hinds were clear. Mating occurred most often during the 3 hours after sundown. In the dark the old stags often sparred and their activity towards females seemed to be weaker than in the daylight hours. During the peak rut the stags were observed to spar only while the females were resting.